Pharmacological inhibition of PHOSPHO1 suppresses vascular smooth muscle cell calcification. (18th December 2012) - Kiffer‐Moreira, Tina; Yadav, Manisha C; Zhu, Dongxing; Narisawa, Sonoko; Sheen, Campbell; Stec, Boguslaw; Cosford, Nicholas D; Dahl, Russell; Farquharson, Colin; Hoylaerts, Marc F; MacRae, Vicky E; Millán, José Luis
Abstract: Medial vascular calcification (MVC) is common in patients with chronic kidney disease, obesity, and aging. MVC is an actively regulated process that resembles skeletal mineralization, resulting from chondro‐osteogenic transformation of vascular smooth muscle cells (VSMCs). Here, we used mineralizing murine VSMCs to study the expression of PHOSPHO1, a phosphatase that participates in the first step of matrix vesicles‐mediated initiation of mineralization during endochondral ossification. Wild‐type (WT) VSMCs cultured under calcifying conditions exhibited increased Phospho1 gene expression and Phospho1 –/– VSMCs failed to mineralize in vitro. Using natural PHOSPHO1 substrates, potent and specific inhibitors of PHOSPHO1 were identified via high‐throughput screening and mechanistic analysis and two of these inhibitors, designated MLS‐0390838 and MLS‐0263839, were selected for further analysis. Their effectiveness in preventing VSMC calcification by targeting PHOSPHO1 function was assessed, alone and in combination with a potent tissue‐nonspecific alkaline phosphatase (TNAP) inhibitor MLS‐0038949. PHOSPHO1 inhibition by MLS‐0263839 in mineralizing WT cells (cultured with added inorganic phosphate) reduced calcification in culture to 41.8% ± 2.0% of control. Combined inhibition of PHOSPHO1 by MLS‐0263839 and TNAP by MLS‐0038949 significantly reduced calcification to 20.9% ± 0.74% of control. Furthermore, the dual inhibition strategy affected the expression of several mineralization‐related enzymes while increasing expression of the smooth muscle cell marker Acta2 . We conclude that PHOSPHO1 plays a critical role in VSMC mineralization and that "phosphatase inhibition" may be a useful therapeutic strategy to reduce MVC. © 2013 American Society for Bone and Mineral Research